The Influence of Information Technology and Monitoring Systems on the Quality of Financial Reports at Bapenda Sumedang Regency - Yuniawati, Ayi Srie; Nurachman, Maman; Fadila, Syarah Nur (SINTESA, 2025)
The term "quality of financial reports" describes a well-organized document that provides information that is simple to understand and can be used as a foundation for future decision-making. It shows the financial condition, transactional activities, and financial performance of local governments. Reliability, understandability, comparability, and relevance are all requirements for a high-quality financial report. The purpose of this study is to investigate how Bapenda's financial reports are affected by regional financial supervision and information technology. 62 respondents were given questionnaires as part of the study, which was carried out at the Sumedang Regency's Regional Revenue Agency (Bapenda). In this study, a quantitative methodology was used. SPSS version 27 was used to process the data, which included descriptive statistical analysis, tests for validity and reliability, and traditional assumption testing, such as tests for heteroscedasticity, multicollinearity, and normality. Multiple linear regression analysis, t-tests, F-tests, and coefficient of determination tests were used to test the hypotheses. Information technology and financial oversight both have a favorable impact on the quality of financial reporting, according to the results of the partial test (t-test). Furthermore, the simultaneous test (F-test) showed that both factors work together to improve the caliber of financial reporting. These results imply that raising the caliber of local government financial reports is facilitated by advancements in financial supervision and information technology.